2008
DOI: 10.1002/gps.2056
|View full text |Cite
|
Sign up to set email alerts
|

A revisit on older adults suicides and Severe Acute Respiratory Syndrome (SARS) epidemic in Hong Kong

Abstract: The SARS epidemic was associated with an increase in older adults' suicide rate in April 2003 and some suicide deaths in June 2003 might have been brought forward. Moreover, an increase in the annual older adults' suicide rate in 2003 was observed and the rate in 2004 did not return to the level of 2002. Loneliness and disconnectedness among the older adults in the community were likely to be associated with the excess older adults' suicides in 2003. Maintaining and enhancing mental well being of the public ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
347
4
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(392 citation statements)
references
References 10 publications
16
347
4
9
Order By: Relevance
“…Indeed, the threat of SARS in Canada was extremely low, with only 43 deaths (World Health Organization) in a nation of over 31 million people-a much smaller risk than driving a motor vehicle. In Hong kong, where the threat of SARS was greater, worry and fear of contracting disease (rather than actual illness) was associated with heightened rates of suicide in older adults, possibly due to reduced social contact and feared stigma of disease (Cheung, Chau, & Yip, 2008). It is interesting to note that disgust likely plays a strong role in social avoidance and stigma, in addition to anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the threat of SARS in Canada was extremely low, with only 43 deaths (World Health Organization) in a nation of over 31 million people-a much smaller risk than driving a motor vehicle. In Hong kong, where the threat of SARS was greater, worry and fear of contracting disease (rather than actual illness) was associated with heightened rates of suicide in older adults, possibly due to reduced social contact and feared stigma of disease (Cheung, Chau, & Yip, 2008). It is interesting to note that disgust likely plays a strong role in social avoidance and stigma, in addition to anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…2004), suicide ideation, mental illness, personality vulnerability, functional impairment, low resilience (Heisel 2006), hopelessness (Cheung et al. 2006), loneliness and disconnectedness from the community (Cheung et al. 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It was speculated that the aftermath effects of SARS such as mass pessimism and fear of the epidemic returning were carried through 2004, accounting for the relatively high suicide rates in older adults that year. 35 Our Poisson regression analysis showed that a steady trough level of suicide rates among old-old women (aged 85 years and older) was not reached until 2002. This observation suggests that ESPP (in place since 2002) may offer added benefit to the oldold adults who would not seek help from the standard psychogeriatric service.…”
Section: Potential Implications For Suicide Prevention In Later Lifementioning
confidence: 85%